Synthesis and characterization of new pyridine-based chiral calamitic liquid crystals - Vardar, Deniz; Ocak, Hale; Akdas Kilic, Huriye; Jeannin, Olivier; Camerel, Franck; Eran, Belkiz Bilgin (TAYLOR & FRANCIS LTD, 2021)
In this paper, novel chiral calamitic compounds, consisting ofn-dodecyloxyphenyl substituted pyridine carboxylate core linked to one or two benzene rings through ester linkers have been synthesised by multi-step procedures. The other end has been varied by introducing a flexible (S)-2-methylbutyloxy or (S)-3,7-dimethyloctyloxy chiral chain. The liquid crystal properties of new compounds were investigated by various experimental techniques such as DSC, POM and SAXS. The pyridine-based calamitic compounds exhibited enantiotropic chiral smectic mesophases such as SmC*, SmA or uncharacteristic mesophase depending on hetero aromatic rings such as nicotinate or picolinate cores, number of aromatic rings and the type of chiral-branched chain.
Keywords: Liquid crystal; pyridine; calamitic compounds; nicotinate; picolinate; chiral chain; BEHAVIOR; SERIES; Chemistry; Crystallography; Materials Science